2020
DOI: 10.1111/dmcn.14772
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy interventions to improve sitting ability in children with or at‐risk for cerebral palsy: a systematic review and meta‐analysis

Abstract: Aim To conduct a systematic review and meta‐analysis on the effectiveness of physical therapy interventions to improve sitting ability in young children with or at risk for cerebral palsy (CP). Method A systematic literature search was performed using five databases. Study selection criteria were randomized controlled trials published in English on physical therapy interventions targeting sitting, reporting developmental or functional sitting outcomes, and focused on young children with or at risk for CP (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…This diversity habitually demands for tailored therapy that is not easily accessible, especially in low-resource and/or rural settings. Then, this heterogeneity is consistent with the plethora of interventions available that are hard to standardize precisely because of the diversity of patients, their needs, environments, and resources, among other aspects [36][37][38][39] .…”
Section: Discussionmentioning
confidence: 53%
“…This diversity habitually demands for tailored therapy that is not easily accessible, especially in low-resource and/or rural settings. Then, this heterogeneity is consistent with the plethora of interventions available that are hard to standardize precisely because of the diversity of patients, their needs, environments, and resources, among other aspects [36][37][38][39] .…”
Section: Discussionmentioning
confidence: 53%
“…The relative disadvantage of supported compared to independent sitting suggests that finding ways to provide this experience while keeping caregivers’ hands free and promoting face‐to‐face orientations may be important. The third is to aggressively employ interventions to improve postural skill (Inamdar, Molinini, Panibatla, Chow, & Dusing, 2020) so that infants learn to sit more quickly; such interventions should include integration of cognitive opportunities into sitting practice (Harbourne et al., 2021). These approaches are not mutually exclusive, and the optimal intervention to promote learning in infants with neuromotor disorders likely includes a combination of all three strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Once we looked up the review articles on KT published over the past 5 years through the Medical Literature Analysis and Retrieval System Online (MEDLINE) (accessed via PubMed), a total of 52 studies were identified. Most of 52 studies are on cerebral palsy [13][14][15], low back pain [16][17][18][19][20][21][22][23], ankle functional performance [24][25][26], knee osteoarthritis (OA) [27][28][29][30][31][32][33], shoulder pain and disability [34][35][36][37][38], breast lymphedema [7,39], rehabilitation after stroke [40][41][42] and so on; however, there are only four studies related to edema [43][44][45][46]. Therefore, the purpose of this study was to review the literature on KT for reducing edema caused by musculoskeletal disorders and investigate whether the use of KT have any effects on controlling edema.…”
Section: Introductionmentioning
confidence: 99%